Open-ended Modelling Problems - Swenson, Jessica (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This Practice Paper conversation describes the intentions, learning objectives, guidelines for problem design, and best practices for implementing Open-ended Modelling problems (OEMPs). OEMPs are ill-defined mathematical modelling problems assigned in the technical core engineering courses with the goal of engaging students in the practice of engineering judgment. This collaborative project, started in 2018, includes engineering education researchers studying student learning and practices and instructors iterating on problem design and implementation. While a significant amount of our project work focuses on students’ learning and thinking, this paper is designed for engineering faculty interested in implementing similar problems within their classes.